MANAJEMEN PELAYANAN IBADAH HAJI DISABILITAS DI KANTOR KEMENTRIAN AGAMA KOTA BIMA - Asykin, Azratal (Mudabbir: Jurnal Manajemen Dakwah, 2024)
Management is important to determine and achieve the goals of an institutionin providing services. Hajj is a form of worship in Islamic law. Not all Hajj pilgrims have thesame or normal physique, but the opposite, especially Hajj pilgrims with physical disabilities.Hajj pilgrims with physical disabilities definitely need more services than Hajj pilgrims whohave normal physical abilities. Hajj pilgrims with disabilities are one of the government’spriorities in organizing the Hajj pilgrimage. The implementation of the Hajj is said to bevalid if it complies with the order of implementation of the pillars of Hajj. This researchuses a descriptive qualitative method, namely observation, interviews and documentation.The aim of writing this thesis is to provide an explanation regarding the services providedby the government to Hajj pilgrims with disabilities during the Hajj pilgrimage. The resultof this writing is to provide an explanation regarding the management of Hajj services forpeople with disabilities.